2018
DOI: 10.1021/acschembio.8b00107
|View full text |Cite
|
Sign up to set email alerts
|

A Switchable Site-Specific Antibody Conjugate

Abstract: Genetic incorporation of unnatural amino acids (UAAs) provides a unique approach to the synthesis of site-specific antibody conjugates that are homogeneous and better defined constructs than random conjugates. Yet, the yield varies for every antibody, and the process is costly and time-consuming. We have developed a switchable αGCN4-Fab conjugate that incorporates UAA p-acetylphenylalanine. The GCN4 peptide is used as a switch, and antibodies fused by GCN4 can direct the αGCN4-Fab conjugate to target different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
(85 reference statements)
0
19
0
Order By: Relevance
“…With DUPA conjugating to pAcF site-specifically expressed on anti-CD3 Fab, the EC 50 of the conjugate has been reduced to 100pM, and serum half-life has been improved to 5–6 h, resulting effective in a treatment in prostate cancer xenograft mouse models [ 81 ]. Same strategy was also employed to synthesize an anti-CD3 Fab-folate conjugate [ 82 ] and a switchable αGCN4-Fab conjugate [ 83 ].…”
Section: Bispecific Antibody (Bsab)mentioning
confidence: 99%
“…With DUPA conjugating to pAcF site-specifically expressed on anti-CD3 Fab, the EC 50 of the conjugate has been reduced to 100pM, and serum half-life has been improved to 5–6 h, resulting effective in a treatment in prostate cancer xenograft mouse models [ 81 ]. Same strategy was also employed to synthesize an anti-CD3 Fab-folate conjugate [ 82 ] and a switchable αGCN4-Fab conjugate [ 83 ].…”
Section: Bispecific Antibody (Bsab)mentioning
confidence: 99%
“…51 The plasmid (pBAD_αPD-L1) was constructed to harbor the heavy-and lambda light chain genes of the Fab fragment following a stll signal peptide. 36,52 The wild type αPD-L1 Fab was expressed in Escherichia coli, with a yield of 4.2 mg/L in shake flask cultures. Sodium dodecyl sulfate/ polyacrylamide gel electrophoresis (SDS/PAGE) analysis showed that the Fab fragment migrated as a single band, with >95% purity and a molecular mass of ∼45 kDa (Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…33,34 In this approach, the amber stop codon employs paired orthogonal amino-acyl transferase and iso-tRNA to incorporate the desired UAA site specifically into proteins including the recombinant antibody. 33,34 Antibodies incorporating UAAs, such as pacetylphenylalanine (pAcF), can be coupled to small molecules of interest via a stable linkage, 29,35,36 generating site-specific therapeutics in high yields. The UAA conjugates as therapeutic candidates have demonstrated superior in vivo efficacy, stability, and toxicology profiles to the cysteine conjugates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently there are 2 strategies: site-specific conjugation technology and chemical structural modification of the linker‒antibody attachment. Site-specific conjugation through antibody engineering is extensively reviewed elsewhere 60 , 61 , 62 .…”
Section: Linker‒antibody Attachments Of the Linkermentioning
confidence: 99%